Cohort study on the factors associated with survival post-cardiac arrest - Vancini-Campanharo, Cássia Regina; Vancini, Rodrigo Luiz; Lira, Claudio Andre Barbosa de; Andrade, Marília dos Santos; Góis, Aécio Flávio Teixeira de; Atallah, Álvaro Nagib (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Cardiac arrest is a common occurrence, and even with efficient emergency treatment, it is associated with a poor prognosis. Identification of predictors of survival after cardiopul-monary resuscitation may provide important information for the healthcare team and family. The aim of this study was to identify factors associated with the survival of patients treated for cardiac arrest, after a one-year follow-up period. DESIGN AND SETTING: Prospective cohort study conducted in the emergency department of a Brazilian university hospital. METHODS: The inclusion criterion was that the patients presented cardiac arrest that was treated in the emergency department (n = 285). Data were collected using the In-hospital Utstein Style template. Cox regression was used to determine which variables were associated with the survival rate (with 95% sig-nificance level). RESULTS: After one year, the survival rate was low. Among the patients treated, 39.6% experienced a re-turn of spontaneous circulation; 18.6% survived for 24 hours and of these, 5.6% were discharged and 4.5% were alive after one year of follow-up. Patients with pulseless electrical activity were half as likely to survive as patients with ventricular fibrillation. For patients with asystole, the survival rate was 3.5 times lower than that of patients with pulseless electrical activity. CONCLUSIONS: The initial cardiac rhythm was the best predictor of patient survival. Compared with ven-tricular fibrillation, pulseless electrical activity was associated with shorter survival times. In turn, compared with pulseless electrical activity, asystole was associated with an even lower survival rate.